European Integration and the Challenges Confronting the social Policy of Bulgaria (UNWE Yearbook, 2005)
The paper reviews the main guidelines of the social policy of the European Union and the important stages of social integration processes and outlines the practical initiatives on the part of Bulgaria necessary for the preparation of the country for the full membership in the EU. It is emphasized that coordinating Bulgaria social legislation with that of the European Union is only a first step in the integration processes per se. The research specifies the reasons why Bulgaria is lagging behind in the social sphere, and the findings underlie several principal challenges for the social policy of Bulgaria.These challenges may be formulated as follows: in social and political practice the point of departure should be viewed as a trinity of “education-employment-living standard”. Prerequisites for a higher quality of life for Bulgarian citizens should be created bearing in mind limited financial resources for health care, education and safety; social policy should turn into a factor of productivity which means new input into the human capital. The new challenges require a change in the quality of the very system of social safety which should envisage safeguards to motivate and encourage people to be more active and independent. As a conclusion the author argues that while adopting the principles and the spirit of the European social policy as a whole, Bulgaria should comply with the national characteristics, traditions and positive precedents of the past.